2022
DOI: 10.1039/d2bm00315e
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle personalized biomolecular corona: implications of pre-existing conditions for immunomodulation and cancer

Abstract: Nanoparticles (NPs) have demonstrated great promise as immunotherapies for applications ranging from cancer, autoimmunity, and infectious disease. Upon encountering biological fluids, NPs rapidly adsorb biomolecules, forming the “biomolecular corona” (BC),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 81 publications
1
0
0
Order By: Relevance
“…However, our results differed from previously reported results for LNPs that showed that p K a values around 9 led to increased lung selectivity, whereas the p K a for the polymers used in our studies were ≤5 (Figure S6). Several factors may play a role in the observed differences between our findings and LNPs, including differential uptake and trafficking mechanisms (Figure ), differential protein corona fingerprints, and other physicochemical properties including size and zeta potential. , Taken together, these results support that the physicochemical properties of polyMDET-C4/mRNA and polyMDET-C6/mRNA polyplexes played a major role in determining the lung selectivity of FLuc expression.…”
Section: Resultssupporting
confidence: 64%
“…However, our results differed from previously reported results for LNPs that showed that p K a values around 9 led to increased lung selectivity, whereas the p K a for the polymers used in our studies were ≤5 (Figure S6). Several factors may play a role in the observed differences between our findings and LNPs, including differential uptake and trafficking mechanisms (Figure ), differential protein corona fingerprints, and other physicochemical properties including size and zeta potential. , Taken together, these results support that the physicochemical properties of polyMDET-C4/mRNA and polyMDET-C6/mRNA polyplexes played a major role in determining the lung selectivity of FLuc expression.…”
Section: Resultssupporting
confidence: 64%